Universities as public institutions - Beteille, Andre (2005)
The democratisation of the Indian university, enabling more social classes to gain access to higher learning, has not always been a smooth process and its consequences, at least in the short run, have not always been beneficial. But as seen in the instance of the European universities between the mid-19th and mid-20th centuries, when institutes of learning become socially more inclusive, they also gain academically in the long run. Much depends, however, on the process of becoming socially inclusive and the forces that drive this process. For such an undertaking to be successful, the tensions between demands of social inclusion and those of academic discrimination need to be tackled convincingly. - Reproduced.
Keywords: Public institutions; Universities